The Effect of Kupang Seafood's Mercury Level on Consumers' Blood Mercury Level at Bursa Kupang Sidoarjo - Maulidiana Puspitasari (JURNAL KESEHATAN LINGKUNGAN, 2019)
Mercury pollution from industrial waste has long been indicated as harmful to environment and human health. Sidoarjo is an industrial city whose water source contaminated with heavy metal mercury and can pollute the living biota around, including kupang fish. Kupang is the main raw material for Sidoarjo's signature foods, unfortunately numbers of health problems to consumers are notified if the mercury from kupang enters human body. The aims of this research is first to analyze the effect of mercury levels in kupang toward mercury levels in consumer's blood, second aim is to analyze the differences of mercury level in consumers and non-consumers' blood. This research was a cross-sectional design under observational research framework. The dependent variable is the mercury level in the respondent's blood while the independent variable is the mercury level in lontong kupang seafood. The variables were measured by questionnaire and examination of mercury levels in blood were performed to 20 respondents. The exposure or independent variable was measured from Mercury levels in kupang. The statistical method used was is linear regression to see the effect of mercury level in kupang seafood toward mercury level in comsumers's blood; and t-test was adopted to see the difference between mercury levels in consumers and non-consumers blood. It was found that, lontong kupang seafood produced in Sentra Kupang Gedangan contained mercury level in average of 0.0098 mg/L. While, mercury levels in respondents's blood were under the standard of 5 µg/L. Blood mercury levels amongst kupang seafood consumers was 0.485 µg/L in average, while blood mercury level amongst non-consumers was 0.0792 µg/L in average. The result of liniear regression test suggested that there is no significant effect from kupang's mercury level toward consumers' blood mercury level. Nevertheless, there is significant differences between mercury level between exposed and non-exposed group. The conclusion of this research. There is significant difference in mercury blood level of being the consumers of kupang seafood rather than non-consumers, it is therefore necessary to raise awareness and educate population regarding the hazard behind the delicacy of kupang